PENGEMBANGAN STUDI TAFSIR DI STAIN SAMARINDA DENGAN PENDEKATAN FENOMENOLOGI - Hadi Mutamam; Subhan Subhan (IAIN Purwokerto, 2015)
Abstract: The results of this study show that: [1] Syllabus economic commentary verses referenced to assess the economic interpretation of passages deemed good enough, as a provision for students in following subsequent courses related to economics. However, the interpretation of the economic verses is not enough to just one semester, because quite extensive material about the economy. We recommend that subjects the interpretation of passages tiered economy as some other academic subjects are tiered. [2] The method of discussion, is helping students to add insight and knowledge, including in understanding the interpretation of the economic verses, according to the student's understanding. In the method of discussion, lecturers should require every student to be asked and argued. Lecturers should give freedom to the students to argue in the discussion. [3] The educational background of the student become an obstacle in understanding the interpretation of the verses of the economy, for those who not graduated from a boarding school or madrasah Aliyah [4] Lecturers should consistent to implement attendance and discipline, when making a leaming contract at the first meeting. Keywords: Interpretation Studies, Phenomenology approach